Pengaruh Pembiayaan Mudharabah, NPF, CAR dan FDR Terhadap ROA dengan Dana Pihak Ketiga Sebagai Variabel Moderating Pada Bank Umum Syariah di Indonesia - Wulandari, Masyita (ITB AAS INDONESIA Surakarta, 2024)
This research aims to find out how big the influence of financing is Mudharabah, Problematic Financing, Capital Adequacy Ratio and Financing to Deposits to Return on Assets Ratio with Third Party Funds as Moderating Variables in Sharia Commercial Banks in Indonesia. The data analysis method used is quantitative with secondary data in the form of annual financial reports of Sharia Commercial Banks in Indonesia. 2018-2022 with a population of 14 Sharia Commercial Banks and 7 banks that meet the criteria. Sample selection uses the Purposive Sampling. The data analysis used is panel data regression withEviews 12. The results of this research show partially that Financing Mudharabah does not have a significant effect on return on assets, Problematic Financing does not have a significant effect on return on assets, capital adequacy ratio does not have a significant effect on return on assets, financing to savings ratio does not have a significant effect on return on assets. And Financing Mudharabah, Problematic Financing, capital adequacy ratio, and financing to savings ratio simultaneously have no effect on asset returns. Meanwhile, Third Party Funds do not moderate the influence of Financing Mudharabah on asset returns, Third Party Funds do not moderate the Effect of Problematic Financing on asset returns, and Third Party Funds do not moderate the Effect of capital adequacy ratios on asset returns. However, Third Party Funds can moderate the influence of the financing to savings ratio on asset returns.